2010
DOI: 10.3109/10253890903524785
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in hypothalamic–pituitary–adrenal axis function in patients with chronic pain syndrome

Abstract: Chronic pain is often equated with chronic stress yet the relationship between chronic pain and hypothalamic-pituitary-adrenal (HPA) axis activity is poorly understood. The objective of this study was to examine diurnal functioning of the HPA axis in patients with clinically defined non-inflammatory chronic pain syndrome (CPS) compared to controls. The sample consisted of 37 adults with CPS and 47 healthy controls. All participants provided saliva samples at awakening, 12:00, 18:00 and 21:00 h on two consecuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 59 publications
0
17
0
Order By: Relevance
“…The higher rates of depression and anxiety observed in females may be in part explained by sex hormones, as androgens seem to have anxiolytic properties whereas estrogens have been found to enhance HPA activity (Maeng & Milad, ; Turner‐Cobb, Osborn, Silva, Keogh, & Jessop, ). Furthermore, rates of depression in females correlate with hormonal changes, particularly with low levels of estrogen that occur throughout the life cycle (Albert et al, ).…”
Section: Sex Differences In Rates Of Depression and Anxietymentioning
confidence: 99%
“…The higher rates of depression and anxiety observed in females may be in part explained by sex hormones, as androgens seem to have anxiolytic properties whereas estrogens have been found to enhance HPA activity (Maeng & Milad, ; Turner‐Cobb, Osborn, Silva, Keogh, & Jessop, ). Furthermore, rates of depression in females correlate with hormonal changes, particularly with low levels of estrogen that occur throughout the life cycle (Albert et al, ).…”
Section: Sex Differences In Rates Of Depression and Anxietymentioning
confidence: 99%
“…Alternatively, two other studies found basal serum cortisol levels in fibromyalgia patients in the normal range [19,20]. However, the majority of previous studies (n < 100; one larger study: n = 429) found reduced activity and impaired feedback sensitivity of the HPA-axis in chronic pain conditions [13,19,21-26], mostly characterized by low basal levels of cortisol as well as a blunted cortisol response to a variety of stressors and dynamic tests. Although evidence is limited, some studies found increased salivary cortisol levels to be associated with higher pain severity scores among subjects with chronic widespread pain [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…In a review of disparities between the sexes in cortisol responses to pain-related stress, differences were reported to be variable 14 . However, a more recent study of differences in diurnal cortisol patterns between the sexes in people with chronic pain, found that men had lower concentrations in the afternoon 27 . In a previous study of chronic pain in men with OA 13 no differences were found between those with OA and healthy controls and pain severity was not accounted for.…”
Section: Discussionmentioning
confidence: 95%